2020
DOI: 10.1136/postgradmedj-2020-138930
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated variations in liver function parameters: a retrospective study

Abstract: BackgroundCharacteristics of laboratory findings of COVID-19 patients are of great significance for diagnosis and treatment. Studies that have analysed the variations in hepatic profile in correlation with the inflammatory markers in SARS-CoV-2 are limited.MethodsWe retrospectively analysed liver function tests and inflammatory markers of 170 admitted patients with confirmed COVID-19 in the tertiary care centre, Post Graduate Institute of Medical Education and Research (PGIMER), India, using Roche Cobas Autoana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 30 publications
14
39
1
Order By: Relevance
“…Different mechanisms are pointed to the possible effect of the SARS-CoV-2 Virus on liver; the virus could directly affect the hepatocytes or the liver could get injured indirectly through enhanced inflammatory response due to the raised immune markers and drug toxicity that are meant to treat or halt the progression of the disease resulting in liver damage and thereby an increase in liver enzymes [ 31 ]. Raised in liver enzymes associated with more severe disease category is also reported in other studies [ 10 – 15 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Different mechanisms are pointed to the possible effect of the SARS-CoV-2 Virus on liver; the virus could directly affect the hepatocytes or the liver could get injured indirectly through enhanced inflammatory response due to the raised immune markers and drug toxicity that are meant to treat or halt the progression of the disease resulting in liver damage and thereby an increase in liver enzymes [ 31 ]. Raised in liver enzymes associated with more severe disease category is also reported in other studies [ 10 – 15 ].…”
Section: Discussionsupporting
confidence: 83%
“…Deranged cell counts, like anemia, polycythemia, leukopenia and leukocytosis with neutrophil predominance and decreased platelet count are found to be associated with severe disease and worse outcome in hospitalized patients [2][3][4][5][6][7][8][9]. Similarly raised liver enzymes and total bilirubin levels were identified in severe and critical patients [6,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms are pointed to the possible effect of the SARS-CoV-2 Virus on liver; the virus could directly affect the hepatocytes or the liver could get injured indirectly through enhanced inflammatory response due to the raised immune markers and drug toxicity that are meant to treat or halt the progression of the disease resulting in liver damage and thereby an increase in liver enzymes (30). Raised in liver enzymes associated with more severe disease category is also reported in other studies (10-15).…”
Section: Discussionsupporting
confidence: 84%
“…Deranged cell counts, like anemia, polycythemia, leukopenia and leukocytosis with neutrophil predominance and decreased platelet count are found to be associated with severe disease and worse outcome in hospitalized patients (2)(3)(4)(5)(6)(7)(8)(9). Similarly raised liver enzymes and total bilirubin levels were identified in severe and critical patients (6,(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 97%
“… 20 Saini et al retrospectively analysed liver function tests of 170 patients with confirmed COVID-19, and also found number of patients with raised levels of any of the liver enzymes were 89 (58.5%), out of which 43 (48.31%) had liver injury, which manifested as increased severity in terms of ICU requirement (p=0.0005). 22 In this study, abnormal liver parameters during hospitalization are associated with illness severity and mortality of COVID-19, with the strongest associations observed between peak liver tests and severe COVID-19, as well as peak liver tests and death. Based on previous studies and our results, we suggested monitoring levels of liver function parameters, which could assist in the optimum management of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 59%